2008
DOI: 10.1016/j.juro.2007.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Pig Kidney: Anatomical Relationships Between the Renal Venous Arrangement and the Kidney Collecting System

Abstract: Although some results of intrarenal venous arrangement in pigs could not be completely transposed to humans, many similarities of pig and human kidneys support its use as the best animal model for urological procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…As opposed to the unipapillary structure of the rodent kidney, pigs have multipapillary kidneys similar to humans. The size of the kidney, the collecting system and the predominantly short-looped nephrons closely resemble the anatomical and physiological features of the human kidney (Sampaio et al, 1998;EskildJensen et al, 2007;Bagetti Filho et al, 2008). In view of the above, our study may be also useful for designing further studies in human medicine.…”
Section: Introductionsupporting
confidence: 64%
“…As opposed to the unipapillary structure of the rodent kidney, pigs have multipapillary kidneys similar to humans. The size of the kidney, the collecting system and the predominantly short-looped nephrons closely resemble the anatomical and physiological features of the human kidney (Sampaio et al, 1998;EskildJensen et al, 2007;Bagetti Filho et al, 2008). In view of the above, our study may be also useful for designing further studies in human medicine.…”
Section: Introductionsupporting
confidence: 64%
“…Morphometric studies of the RAs in pigs have not been reported despite its importance for the implementation of experimental and hemodynamic procedures using the vascular components of the urinary system of the pig (Kaouk et al, 2003;Hammond et al, 2004;Bagetti Filho et al, 2008). In addition, the characterization of the RA and its branches in pigs enriches the teaching-learning processes of compared anatomy with this species.…”
Section: Introductionmentioning
confidence: 99%
“…Bagetti Filho et al [1] examined swine kidneys and made similar observations. They noted, that major of tributaries of the renal vein, i.e.…”
Section: Discussionmentioning
confidence: 65%
“…IVs, are located close to the ventral side of the renal pelvis. Bagetti Filho et al [1] mentions a small percentage (3.28% of cases) of major venous trunks, which run close to the dorsal side of the renal pelvis and which are directly inserted in the renal vein. In the studied material, the primary IVs inserted in the secondary IVs are the only veins, which can run close to the dorsal side of the renal pelvis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation